2022
DOI: 10.3390/molecules27082410
|View full text |Cite
|
Sign up to set email alerts
|

The Phenolics and Antioxidant Properties of Black and Purple versus White Eggplant Cultivars

Abstract: The total phenolic content, anthocyanins, phenolic acids, antioxidant capacity and α-amylase inhibitory activity of black (Aydin Siyahi), purple (Kadife Kemer) and white (Trabzon Kadife) eggplants grown in Turkey were subjected to a comparative investigation. The black cultivar exhibited the highest total phenolic (17,193 and 6552 mg gallic acid equivalent/kg fw), flavonoid (3019 and 1160 quercetin equivalent/kg fw) and anthocyanin (1686 and 6167 g delphinidin-3-O-glucoside equivalent/kg fw) contents in crude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…This was suggested to result from the novo synthesis of Maillard intermediates with antioxidant properties. In similar study, Nesrin, et al [90] found that the crude phenolic extracts of the eggplants fruit parts (peel and pulp) exhibited high antioxidant and scavenging activities which correlated with the cultivars. The black and purple eggplants are the cultivars with greater potential benefits in terms of their phenolics and antioxidant values than the white eggplant.…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 84%
See 3 more Smart Citations
“…This was suggested to result from the novo synthesis of Maillard intermediates with antioxidant properties. In similar study, Nesrin, et al [90] found that the crude phenolic extracts of the eggplants fruit parts (peel and pulp) exhibited high antioxidant and scavenging activities which correlated with the cultivars. The black and purple eggplants are the cultivars with greater potential benefits in terms of their phenolics and antioxidant values than the white eggplant.…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 84%
“…Total phenolics, β-carotene, flavonoids and anthocyanins were determined in eggplant fruits as shown in Table (4). Phenolics was reported the most abundant ones, followed by anthocyanins, flavonoids and β-carotene.…”
Section: Bioactive Compounds and Antioxidant Capacity In Eggplant Fruitsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vegetables, TAC levels around 150 mg C3G per 100 g fw are found in eggplant, purple sweet potato, and red cabbage. Among anthocyanins, delphinidin 3-O-rutinoside is the predominant one in eggplant [78], while 3-O-sophoroside-5-glucoside derivatives of peonidin and cyanidin are the most important in purple sweet potato [79]. On the other hand, cyanidin-3-diglucoside-5-glucoside, cyanidin-3-(sinapoyl)(sinapoyl)-diglucoside-5-glucoside and cyanidin-3-(ρ-coumaroyl)-diglucoside-5-glucoside are most commonly in red cabbage [80].…”
Section: Anthocyanins Rich-sourcesmentioning
confidence: 99%